2014
DOI: 10.4081/oncol.2014.259
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid hemangioendothelioma: an overview and update on a rare vascular tumor

Abstract: Epithelioid hemangioendothelioma is a rare vascular tumor, described for the first time in 1975 by Dail and Liebow as an aggressive bronchoalveolar cell carcinoma. The etiology is still a dilemma. Studies about suggestive hypothesis are ongoing. Most of the times it affects lung, liver and bones, although this kind of tumor may involve the head and neck area, breast, lymph nodes, mediastinum, brain and meninges, the spine, skin, abdomen and many other sites. Because of its heterogeneous presentation, as it rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
338
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(354 citation statements)
references
References 70 publications
6
338
0
10
Order By: Relevance
“…According to the literature, approximately 248 cases of PEH have been reported [5] and some cases have been diagnosed based on findings of a solitary lung mass or multiple pulmonary nodules with no other primary malignancy [6,7]. This is the first report of multiple pulmonary nodules found in a patient diagnosed with both colon cancer and breast cancer, which were misidentified as metastasis.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…According to the literature, approximately 248 cases of PEH have been reported [5] and some cases have been diagnosed based on findings of a solitary lung mass or multiple pulmonary nodules with no other primary malignancy [6,7]. This is the first report of multiple pulmonary nodules found in a patient diagnosed with both colon cancer and breast cancer, which were misidentified as metastasis.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have reported a 5-year survival probability of 60% (range, 47-71%) [13] and median survival of asymptomatic PEH patients was 180 months [5]. The prognostic factors of PEH have not yet been established either.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations